2023
DOI: 10.3389/fimmu.2023.1086280
|View full text |Cite
|
Sign up to set email alerts
|

RUNX1/CD44 axis regulates the proliferation, migration, and immunotherapy of gliomas: A single-cell sequencing analysis

Abstract: BackgroundGlioma is one of the most common, primary, and lethal adult brain tumors because of its extreme aggressiveness and poor prognosis. Several recent studies relevant to the immune function of CD44, a transmembrane glycoprotein as a significant hyaluronic acid receptor, have achieved great success, revealing the critical role of CD44 in immune infiltration in gliomas. The overexpression of CD44 has been verified to correlate with cancer aggressiveness and migration, while the clinical and immune features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…We used the oncoPredict R package to analyze drug response data from the Genomics of Drug Sensitivity in Cancer (GDSC) database (http://www.cancerRxgene.org) to investigate the relationship between chemotherapeutic sensitivity and the prognostic model [23 – 25]. The Wilcoxon rank‐sum test was used to compare the chemotherapeutic sensitivity of patients to these drugs between the SPDL1‐high and SPDL1‐low expression groups.…”
Section: Methodsmentioning
confidence: 99%
“…We used the oncoPredict R package to analyze drug response data from the Genomics of Drug Sensitivity in Cancer (GDSC) database (http://www.cancerRxgene.org) to investigate the relationship between chemotherapeutic sensitivity and the prognostic model [23 – 25]. The Wilcoxon rank‐sum test was used to compare the chemotherapeutic sensitivity of patients to these drugs between the SPDL1‐high and SPDL1‐low expression groups.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that overexpression of CD44 is linked to poor prognosis, 39 tumor progression, 40 and aggressive behavior 41 of tumors. For instance, CD44 is a possible CSCs marker in meningioma; the high expression of CD44 was associated with a shorter progression‐free survival 42 .…”
Section: Cd44 In Neoplastic Diseasesmentioning
confidence: 99%